Penggunaan Media Pembelajaran dengan Benda Konkret untuk Meningkatkan Kemampuan Berhitung pada Peserta Didik Kelas II - Jahyus, Muhammad Ryan; Dzulqadri, Abrar; Febrian, Deni; Febrian, Febrian (TSAQOFAH, 2023)
Learning outcomes are described as written statements of what a learner is expected to know, understand and/or be able to do at the end of a period of learning", which means that learning outcomes are statements about what students are expected to know at the end of learning Learning media in education is something that absolutely must be used in achieving learning goals. Today's reluctance to use media is widely felt by teachers for complicated and troublesome reasons. Concrete media is the easiest tool to use, because we don't need to make any preparations other than using it right away. What is meant by real objects as media are tools for conveying information in the form of real or original objects or objects that have not undergone significant changes. Based on some of the definitions above, it can be concluded that these concrete objects are actual objects, objects or media that help students' real experiences.